کەلتورى ئاشتى لەکۆمەڵگەى کوردیدا لەڕوانگەى دەستەبژێرەوە (توێژینەوەیەکى مەیدانییە لە هەرێمى کوردستان) (توێژینەوەی هەڵێنجراو) - مجید, پەیمان عبدالقادر; حەمەلاو, ئاودێر ئەبوبەکر سید (Sulaimani Journal for Humanities, 2023)
The researcher conducted research entitled (Culture of Peace in Kurdish Society) which the main objective was to know the level of the structure of the culture of peace in Kurdish society with several other sub-objectives such as: including: 1- Identifying the elements of the culture of peace in Kurdish society. 2- Identifying the obstacles and supports in front of the establishment of a culture of peace in Kurdish society. For this purpose, the researcher has taken a number of measures: - Research Method: Qualitative Method / Research Society: All candidates who hold master's and doctoral degrees in the field (political, religious, intellectual) / Sample: There were 17 units of selection in a purposeful manner, all of which were selected on the basis that they are elite (political, religious, intellectual) and at the same time have academic degrees in all four provinces of Kurdistan (Erbil, Suleimani, Duhok, Halabja). 1. Interview: Semi-open interview. 2- Note, (2022 to 2023) The most important results of the study were: 1. According to the respondents, the culture of peace is weak in the Kurdish society, which. 2- (The culture of cooperation) comes first in the ranking of the elements of peace in the Kurdish society. 3-The obstacles to the culture of peace are: - Political instability / the negative role of the media / poor economic situation / weakness of the education system at the community level / the presence of fanaticism and religious extremism., 4. The supports for a culture of peace are: - Moderate adherence to religious principles / media work on general lines, laws and principles of non-violent behavior, justice, equality and equality / health education at the community level / following a moderate policy / following laws and principles of justice and equality. Finally, the researcher presents some recommendations and suggestions.
Keywords: (culture; peace; culture of peace; society